Lumbar Disc Surgery with Epidural Anesthesia: Review of 700 Cases - Albayrak, Serdal; Erol, Fatih S.; Demirel, Ismail; Ayden, Omer; Ucler, Necati (Turkish Neurosurgical Soc, 2016)
AIM: Lumbar disc surgery can be performed under general anesthesia or regional anesthesia methods. There are long-standing discussions between neurosurgeons, orthopedic surgeons and anesthesiologists concerning the use of epidural anesthesia in lumbar surgery. The results of this study's 700 lumbar disc surgery cases operated with epidural anesthesia in our clinic between September 2006 and December 2011 will contribute to these discussions. MATERIAL and METHODS: This study included 700 patients underwent lumbar disc surgery with epidural anesthesia, which consisted of 388 males (55%) and 312 females (45%). Forty-two of these cases had recurrence disc herniation and only 11 of 42 cases were operated in our department. RESULTS: Eleven of 700 cases had dural injury and were repaired intraoperatively by primary sutures and tissue sealants. Infection of the incision site developed in six patients, who healed with appropriate antibiotic treatment with no problems. In addition to those 700 cases, 22 patients received general anesthesia in which we started with epidural anesthesia. Microdiscectomies were performed in 578 of 700 cases, and open surgery in 122 cases. CONCLUSION: This study showed that epidural anesthesia seems more advantageous for some patients since it does not have some of the risks that general anesthesia bears.
Keywords: Epidural anesthesia; Lumbar disc surgery; General anesthesia